Chinese heritage language motivation: a study of motivation development in a multicultural context - Wen, Xiaohong (Frontiers in Psychology, 2024)
This study investigated motivation of Chinese heritage language (CHL) learners with diverse Chinese language backgrounds at an American university. Using a mixed-methods design, it examined the factors that motivated CHL learners to enroll in Chinese courses and continue their studies. The Study explored interactions that enhanced the learning experience and self identity development. A survey was conducted, followed by individual interviews. The results identified five motivation factors significantly correlated to the ideal L2 self, which functions as an anchor. The ideal L2 self was the strongest predictor of intended effort via positive attitude. The classroom-related experience was another significant predictor of intended effort. Interview data highlighted the dynamic interplay between sociocultural contexts and learner-environment interactions which provokes motivation development and strengthens identity reconstruction and future self-guides. In the process, the learner continuously constructs and consolidates the identity as "Chinese" relating to family and culture. Lastly, the anti-ought-to L2 self, characterized by reactions to "others", emerged in dynamic interactions between learners and contexts. This motive inspired the learner to continuously develop the possible self and gain positive learning experiences.